Microenvironment Matters: Copper–Carbon Composites Enable a Highly Efficient Carbon Dioxide Reduction Reaction to C2 Products - Shen, Yu-Jhih; Hsu, Yung-Hsi; Chang, Yu-Chia; Ma, Jian-Jie; Peng, Kang-Shun; Lu, Ying-Rui; Hsu, Shao-Hui; Hung, Sung-Fu (ACS applied materials & interfaces, 2025)
Copper is the catalyst widely used to produce multicarbon products for the carbon dioxide reduction reaction (CO2RR). The surrounding microenvironment of copper plays a crucial role in determining its catalytic activity and selectivity. In this study, we compare three copper electrocatalysts with different microenvironments: pure metallic copper, a copper metal–organic framework (MOF), and a MOF-derived copper–carbon composite. Operando X-ray absorption spectroscopy, transmission electron microscopy, and Raman spectroscopy reveal that copper in the copper–carbon composite remains in a metallic state, encapsulated by a carbon matrix. The composite catalyst achieves a Faradaic efficiency of 75.6% for C2 products, including ethylene and ethanol, at a current density of 500 mA cm–2, with a C2 current density of 377.9 mA cm–2. This performance suppresses pure metallic copper, which reaches an optimal Faradaic efficiency of 64.5% for C2 products at a current density of 300 mA cm–2, with a C2 current density of 193.5 mA cm–2. The copper–carbon composite also significantly overperforms the copper-MOF catalyst, which shows an optimal Faradaic efficiency of 52.0% for C2 products at a current density of 400 mA cm–2, with a C2 current density of 208.0 mA cm–2. These findings highlight the importance of the microenvironment near active copper sites in determining CO2RR efficiency. We hope that our results provide valuable insights for advancing catalyst design in carbon dioxide reduction, contributing to reduced carbon emissions and improved environmental sustainability.